2019
DOI: 10.1111/jgh.14651
|View full text |Cite
|
Sign up to set email alerts
|

Clinical and psychological characteristics in gastroesophageal reflux disease patients overlapping with laryngopharyngeal reflux symptoms

Abstract: Background and Aim Laryngopharyngeal reflux (LPR) defined as reflux of gastric content reaching above the upper esophageal sphincter is frequently found in patients with gastroesophageal reflux disease (GERD). This study aimed to investigate clinical and psychological differences between GERD patients with or without LPR symptoms. Methods This study enrolled 303 consecutive patients with proton pump inhibitor treatment‐naïve scheduled for upper endoscopy because of troublesome reflux symptoms and recognized as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(29 citation statements)
references
References 25 publications
0
29
0
Order By: Relevance
“…Laryngopharyngeal reflux disease (LPRD) comprises a group of symptoms and signs caused by reflux of the gastric contents into the upper esophageal sphincter and is therefore considered an extra-esophageal variant of gastroesophageal reflux disease (GERD). 1,2 However, whether the true pathogenesis of LPRD involves reflux of the gastric contents is unclear. The different symptoms of GERD and LPRD suggest that they are, at least clinically, two different diseases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Laryngopharyngeal reflux disease (LPRD) comprises a group of symptoms and signs caused by reflux of the gastric contents into the upper esophageal sphincter and is therefore considered an extra-esophageal variant of gastroesophageal reflux disease (GERD). 1,2 However, whether the true pathogenesis of LPRD involves reflux of the gastric contents is unclear. The different symptoms of GERD and LPRD suggest that they are, at least clinically, two different diseases.…”
Section: Introductionmentioning
confidence: 99%
“…Nonetheless, the proton pump is central to both LPRD and GERD. [1][2][3]7,8 Whereas the gastric H + /K + ATPase is a well-characterized proton pump mediating gastric acid secretion, [7][8][9] other H + /K + ATPases may be present in organs outside the stomach, such as the larynx. The presence of extra-gastric H + /K + ATPases may explain the clinically significant effect of proton pump inhibitor (PPI) pharmacotherapy in patients with chronic laryngitis related to LPRD but without GERD symptoms.…”
Section: Introductionmentioning
confidence: 99%
“…In the hypotonic UES group, the median of HADS score were for HADS-T 13 (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19), HADS-A 7(5-10) and HADS-D 6(3-8). In the normotonic UES group: for HADS-T 13(9-19), HADS-A 8(5-11) and HADS-D 6(3.75-8).…”
Section: Results Resultsmentioning
confidence: 99%
“…[ 16 ] To date, a few studies describing GERD have shown that psychological factors, particularly anxiety and depression, play an important role in patients with GERD. [ 17 19 ] However, a comprehensive explication of this association had not yet been given. Thus, this study aims to systematically investigate the association between GERD and DD.…”
Section: Introductionmentioning
confidence: 99%